The Errors of the Democratic System According to Pancasila: A Critical Examination of Governance in Indonesia - Iskandarsyah Siregar (Britain International for Academic Research (BIAR-Publisher), 2024)
Democracy, regarded as the epitome of equitable governance, is celebrated for promoting freedom, justice, and equality. However, when Democracy is implemented within the cultural and philosophical framework of Pancasila—Indonesia's foundational ideology—significant tensions emerge. This study delves into these complexities, critically examining how democratic principles intersect with Pancasila's emphasis on consensus, collectivism, and ethical leadership. The analysis identifies critical areas of conflict: The overreliance on majority rule can marginalize minority voices, The prioritization of individualism is often at the expense of social cohesion, and The focus is on popular leadership rather than governance rooted in moral integrity. Additionally, the persistence of economic inequality in a democratic context raises concerns about the system's ability to deliver social justice, a core tenet of Pancasila. The study argues that to serve the interests of the Indonesian people more effectively, Democracy in Indonesia must be recalibrated to align with Pancasila's values. It concludes with recommendations for institutional reforms emphasizing consensus-building, ethical leadership, and equitable resource distribution, aiming to create a governance model that reflects the people's will and upholds the cultural and ethical values central to Indonesia's national identity.